THE GENERAL SECONDARY EDUCATION SYSTEM IN UZBEKISTAN (1991-2025) - Kudratov Azizjon Dehkanboyevich (Web of Journals Publishing, 2025)
Uzbekistan in 1991 to independence after reaching, education the system is also large to changes face came. In particular, the general middle education — that is elementary and of the school middle stage — this period inside structure in terms of, content in terms of and infrastructure in terms of noticeable updates in this article, the years 1991-2025 between general middle education in the field was main changes seeing is released.
Keywords: Constitution, National personnel preparation program, lyceum, college, organizational reforms, innovative technology, continuous education.